Association Between Sarcopenia and Quality of Life in Community-Dwelling Older Adults: Findings From a Cross-Sectional Study - Prima, Ashar; Muhammad Wildan Kamal; Andas, Amzal Mortin; Astuti, Puji; Indah Puspitasari; Ilyas, Asmiana Saputri (Jurnal Berita Ilmu Keperawatan, 2026)
Sarcopenia is common in older adults and contributes to functional decline, disability, and increased healthcare utilization. In community-dwelling older adults, increased risk of sarcopenia may limit daily activities and negatively affect health-related quality of life, yet evidence from community settings in Indonesia remains limited. This study examined the association between risk of sarcopenia and health-related quality of life among community-dwelling older adults. Cross-sectional study conducted in the working area of Wanasari Public Health Center, Bekasi Regency, Indonesia, February–March 2025. Community-dwelling adults aged ≥60 years (n=305) were recruited by consecutive sampling. Risk of sarcopenia was measured using the SARC-CalF (SARC-F plus calf circumference) questionnaire; health-related quality of life was measured with the EQ-5D-5L (EuroQol-5 Dimension, 5-level). Validity and reliability testing of instruments in the study sample are reported in Methods. The association between sarcopenia risk (continuous SARC-CalF score) and EQ-5D index score was assessed with Spearman’s rank correlation. The result showed that Mean age 64.65±5.20 years; 61.3% female. A total of 137/305 (44.9%) were classified as at risk of sarcopenia (SARC-CalF), and 168/305 (55.1%) as low risk. Median (range) SARC-CalF = 4 (0–20). Median EQ-5D index = 0.83 (0.41–1.00). There was a strong, negative correlation between SARC-CalF score and EQ-5D index (Spearman’s rho = –0.711, p<0.001), indicating higher sarcopenia risk relates to lower quality of life. In this community sample, higher risk of sarcopenia is strongly associated with poorer health-related quality of life. We recommend routine screening for sarcopenia risk in primary care and further analytic studies to identify independent predictors in this population